Fostering Self-Authorship and Changemaking : Insights from a Social Entrepreneurship Practicum - Wessels , Anke K.; Brice , Sarah; Chan , Kelsey; Desmond , Emily; Gonzales, Deana; Lee, Chelsea; Stasolla, Ryan (Experiential Learning and Teaching in Higher Education, 2022)
None provided